UPAYA MENINGKATKAN KOMPETENSI PROFESIONAL GURU PAUD MELALUI PENYELENGGARAAN PROGRAM INKLUSIF DI TK AISYIYAH II CIMAHI - sutriawati, Sri; Windarsih, Chandra Asri (IKIP Siliwangi, 2019)
Inclusive education is one of the non-discriminatory education reforms, equating basic rights to change the system from segregation to integration. Efforts to improve and readiness of professional teachers need concrete actions that can support the implementation of inclusive programs in PAUD. Formation and development of professional attitudes through training programs, training, TOT, workshops, lectures, seminars and development of early childhood teachers. The problem is